Innovative strategic planning and international collaboration for the mitigation of global crises - Antošová, Gabriela, 1983- (Practice, progress, and proficiency in sustainability (PPPS) book series., 2022)
"This book is for professionals and academic researchers findings in the field of international strategic management to improve their understanding of the innovative, strategic planning at different levels of the multidisciplinary context of globalization, internationalization, education, tourism, aviation, digitalization, regional economics and statistics, management and marketing, religion, public policy and society"--